2002
DOI: 10.1159/000066169
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy of Machado-Joseph Disease in Taiwan: A Morphometric and Genetic Study

Abstract: Machado-Joseph disease (MJD) is a dominantly inherited cerebellar ataxia associated with spasticity, ophthalmoplegia, dystonia and peripheral neuropathy. Presented here are 5 MJD cases. A morphometric analysis of the histopathology of their sural nerves was carried out to know the relationship between axon size and myelin thickness. MJD cases were identified by polymerase chain reaction. On the basis of the clinical symptoms, there was 1 type I, 2 type II and 2 type III patients. The sural nerves were biopsied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Researchers have reported that a decrease in the number and size of myelinated axons influences the occurrence of peripheral nerve palsy or neuropathy [3][4][5][6], and a lower CR of myelinated axons has been partly implicated in the degeneration of nerve fibers [7]. A smaller NM, ATA, and lower ACR of myelinated axons would help explain the sex difference in the incidence of peripheral nerve palsy and neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have reported that a decrease in the number and size of myelinated axons influences the occurrence of peripheral nerve palsy or neuropathy [3][4][5][6], and a lower CR of myelinated axons has been partly implicated in the degeneration of nerve fibers [7]. A smaller NM, ATA, and lower ACR of myelinated axons would help explain the sex difference in the incidence of peripheral nerve palsy and neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The data on the above pairs of groups were thus independent of the aging process. The methods for preparation of sections, also described in our previous report [1], were as follows: 6. Differentiate in 2% saturated lithium carbonate (= 0.03% Li2CO3) for 60 min 7.…”
Section: Methodsmentioning
confidence: 99%
“…Signs of neurodegeneration are widespread and variable, most often involving deeper structures of the basal ganglia, various brainstem nuclei and the cerebellum (Sequeiros and Coutinho, 1993; Koeppen et al, 1999; Lin and Soong, 2002; Rub et al, 2002a, b; Rub et al, 2003; Rub et al, 2004a, b). Brain atrophy and neuronal loss have been described in many areas, including the globus pallidus, various thalamic nuclei, subthalamic nucleus, substantia nigra, red nucleus, medial longitudinal fasciculus, various pontine nuclei and cranial motor nerve nuclei, superior and middle cerebellar peduncles, cerebellar dentate nucleus, Clarke's column and spinocerebellar tracts, vestibular nucleus, anterior horn cells, posterior columns and posterior root ganglia.…”
Section: Neuropathological Featuresmentioning
confidence: 99%
“…Ataxia, however, never occurs in isolation. Numerous other clinical problems reflect progressive dysfunction in the brainstem, oculomotor system, pyramidal and extrapyramidal pathways, lower motor neurons and peripheral nerves (Sequeiros and Coutinho, 1993; Takiyama et al, 1994; Cancel et al, 1995; Sasaki et al, 1995; Durr et al, 1996; Matsumura et al, 1996; Schols et al, 1996; Soong et al, 1997; Zhou et al, 1997; Watanabe et al, 1998; Friedman, 2002; Lin and Soong, 2002; Rub et al, 2002a,b; Rub et al, 2003; Rub et al, 2004a,b; Friedman et al, 2003). Most commonly, affected persons present in the young-adult to mid-adult years with progressive gait imbalance accompanied by vestibular and speech difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported that a decrease in the number and size of myelinated axons influences the occurrence of peripheral nerve palsy or neuropathy (Korinthenberg et al, 1997; Fukuda et al, 2000; Lin & Soong, 2002; Griffn & Höke, 2005), and a lower circularity ratio of myelinated axons has been partly implicated in the degeneration of nerve fibers (Moriyama et al, 1995). A smaller number, average transverse area, and lower average circularity ratio of myelinated axons would help explain the sex difference in the incidence of peripheral nerve palsy and neuropathy.…”
Section: Discussionmentioning
confidence: 99%